The The Impact Of Business Crimes Due To Abandoned Land Under The Right To Cultivate (HGU) In Indonesia: An Economic Analysis Of Law Approach - Rizal Syamsul Maarif; Henny Nuraeny; Abraham Yazdi Martin; Muhammad Aminulloh; Efridani Lubis (Ann Publisher, 2025)
Background. Richard Posner, in his Economic Analysis of Law, argues that business crimes involving the abandonment of concession lands (Hak Guna Usaha/HGU) reflect the existence of externalities and market failures, where corporate concession holders who neglect their lands cause substantial losses to both the State and society. Aims. This study aims to evaluate the economic and legal impacts of business crimes arising from the abandonment of plantation concession lands (HGU) in Indonesia and to provide alternative policy solutions for resolving this issue. Methods. The research employs a normative legal method with an evaluative approach, examining the phenomenon of abandoned plantation HGU lands from both regulatory and economic perspectives. The analysis seeks to produce concrete recommendations for optimizing the management of abandoned plantation lands through an integration of legal and economic principles. Result. The findings reveal that, as of 2024, the Ministry of Agrarian Affairs and Spatial Planning (ATR/BPN) recorded approximately 1,347,099 hectares of abandoned HGU lands across Indonesia, accumulated between 2020 and 2024. Under existing fiscal regulations, HGU concession holders are required to pay Non-Tax State Revenue (PNBP) of IDR 26,500 per 100 hectares annually. Based on this rate, the total potential State revenue loss due to abandoned HGU lands is estimated at IDR 356,981,235 (three hundred fifty-six million nine hundred eighty-one thousand two hundred thirty-five rupiahs). Conclusion. The study concludes that the widespread abandonment of HGU lands represents a significant economic loss and legal inefficiency. Lands that should generate income for the State instead become sources of conflict, inefficiency, and administrative burden, illustrating the failure of both corporate governance and legal enforcement mechanisms. Implication. The implications of this research emphasize the necessity of developing criminal, civil, and administrative law instruments to prevent and sanction corporate violations that cause State losses. The study proposes the formulation of a criminal law–based regulatory framework as a deterrent mechanism to ensure corporate accountability in land management and to restore the economic and social function of land in accordance with Indonesia’s constitutional mandate